Artificial Intelligence Adoption and Digital Financial Resilience Effects on Performance in Digital-Based Financial Institutions Australia - Paul Gerrans; Frank Liu; Rui Zhong (International Journal Business and Entrepreneurship, 2026)
This study examines the role of artificial intelligence adoption in shaping financial performance through digital financial resilience in digital-based financial institutions in Australia. A quantitative explanatory approach was employed using survey data collected from employees involved in digital and financial operations. Structural Equation Modeling with the Partial Least Squares technique was applied to test the proposed relationships. The results indicate that artificial intelligence adoption has a positive and significant effect on digital financial resilience. Digital financial resilience, in turn, positively influences liquidity, profitability, firm value, and risk management effectiveness. These findings demonstrate that technological capability enhances financial outcomes primarily through adaptive stability rather than through direct effects alone. The study highlights that institutions with stronger resilience are better able to sustain transaction continuity, manage financial risks, and maintain investor confidence. By integrating artificial intelligence adoption and digital financial resilience within a single framework, this research provides a more comprehensive explanation of how digital transformation affects financial sustainability. The findings suggest that successful digital finance strategies require not only advanced analytical systems but also organizational readiness to absorb digital disruptions. This study offers important insights for both scholars and practitioners seeking to understand performance dynamics in technology-driven financial institutions.